Improving the Performance of Pelanusa Group Patchwork and Quilting Craftswomen - Evidence from Mediation Model - Syeikhu Alfa Ridho; Agus Purnomo Sidi; Hazira Binti Saleh (Jurnal Pendidikan Ekonomi, 2024)
Low work motivation, work-life balance, and inadequate job satisfaction are obstacles in improving the performance of patchwork crafters in Malang Regency. This condition has an impact on productivity and product quality, which in turn hinders the growth of the local creative economy. This study aims to analyze the mediating role of job satisfaction in the relationship between work motivation and work-life balance on the performance of patchwork crafters in the Pelanusa Group, Malang Regency. This study uses a quantitative method with a PLS-SEM approach. The research respondents consisted of 120 female patchwork crafters selected through accidental sampling technique. The results showed that work motivation and work-life balance have a significant influence on performance, both directly and through the mediation of job satisfaction. High work motivation increases job satisfaction and performance, while work-life balance contributes to the satisfaction and productivity of patchwork crafters. The findings indicate the importance of creating a work environment that supports work-life balance and recognizes the contribution of crafters to improve the performance and sustainability of the creative economy sector. Keywords: work motivation, work life balance, work satisfaction, work performance